Soybean Cost-Return Budget in Southeast Kansas - Fausett, Marvin R. (My University, 1997)
This publication outlines the expected costs and returns for soybean production in southeast Kansas.
MF994_1997_10
Keywords: MF994; Economics; Crops; MF